The Relationship of Arrogance Leadership, Job Commitment, and Job Satisfaction in Higher Educational Organisations in Sarawak - Thong Sim, Jefferson Poh; Ling, Ying-Leh (Online Journal for TVET Practitioners, 2020)
This is a study about the relationship of arrogance leadership, job commitment and job satisfaction in higher educational organisations in Sarawak. This study looked into whether the level of job commitment and job satisfaction in an organisation is highly related to the type of leadership style portrayed by leaders in higher educational organisations. The descriptive research design was implemented to further understand the correlational relationship between arrogance leadership (independent variable) and job commitment and job satisfaction (dependent variables). The research instrument, a questionnaire through an online platform – Google Form, was distributed from January till February 2020. The data were collected from one hundred and thirty respondents from twenty-one higher educational organisations in Sarawak. The data was analysed using the SPSS software. The findings of this study proved that although the level of arrogance leadership may be at the below average level or at its infancy stage, it is important to note that it exists in higher educational organisations which will significantly affect other variables like job commitment and job satisfaction. This is supported when the findings showed that the overall level of job commitment is also low. Lastly, the findings proved that there are significant relationships between arrogance leadership with job commitment and job satisfaction among the lecturers. Practically, this study is able to help higher educational organisation and its management to identify the level of arrogance leadership, job commitment and job satisfaction within its organisation. Theoretically, on the other hand, this study is unique as it focused on the Malaysian context.